2016
DOI: 10.1155/2016/1060574
|View full text |Cite
|
Sign up to set email alerts
|

Gust Load Alleviation with Robust Control for a Flexible Wing

Abstract: Traditional methods for gust alleviation of aircraft are mostly proposed based on a specific flight condition. In this paper, robust control laws are designed for a large flexible wing with uncertainty in Mach number and dynamic pressure. To accurately describe the aeroelastic model over a large flight envelope, a nonlinear parameter-varying model is developed which is a function of both Mach number and dynamic pressure. Then a linear fractional transformation is established accordingly and a modified model or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Previously, researchers have approached the design of active load alleviation systems in different ways. Rossow et al [26] investigated the feasibility of an aircraft featuring load alleviation technologies; Sun et al [27] looked at active load alleviation from the control system perspective; and Zing et al [28] demonstrated the experimental results of the high aspect-ratio wing wind-tunnel test with active load alleviation while using piezoelectric control. The work of Fezans et al focused on novel sensors and control systems technologies to enable rapid and robust active load alleviation [29][30][31][32].…”
Section: Load Alleviationmentioning
confidence: 99%
“…Previously, researchers have approached the design of active load alleviation systems in different ways. Rossow et al [26] investigated the feasibility of an aircraft featuring load alleviation technologies; Sun et al [27] looked at active load alleviation from the control system perspective; and Zing et al [28] demonstrated the experimental results of the high aspect-ratio wing wind-tunnel test with active load alleviation while using piezoelectric control. The work of Fezans et al focused on novel sensors and control systems technologies to enable rapid and robust active load alleviation [29][30][31][32].…”
Section: Load Alleviationmentioning
confidence: 99%
“…In previous research, [21][22][23][24] the wing root bending moment M y and the rigid-body x r and elastic state x e responses have been selected as the main performance metrics to consider. Consequently, the performance metrics relating to these variables (1, 2, and 5) will be considered to be of most importance.…”
Section: The Euclidean Norm Of the Flight Path Anglementioning
confidence: 99%
“…Many researchers concentrate their direction on the gust load alleviation (GLA) field because of its indispensable role on flight safety and passenger comfort (Smeur et al , 2016; Ferrier et al , 2018; Wang et al ,2017; Grzedziński and Mróz, 2010; Guo et al , 2015; Liu and Sun, 2016; Poussot-Vassal et al , 2017; Tang et al , 2016). As a key branch of GLA design, gust response stabilization (GRS) has attracted more and more scholars’ attention because of flight stability.…”
Section: Introductionmentioning
confidence: 99%